126k views
4 votes
Find the sum of the series and show your process for finding each term leading to the final sum.

∑^5k=3(−2k+5)

Please explain also

1 Answer

1 vote

ANSWER


\sum_(k=3)^5( - 2k + 5) = - 9

Step-by-step explanation

The given series is


\sum_(k=3)^5( - 2k + 5)

This series is finite.

The expanded form is


\sum_(k=3)^5( - 2k + 5) = ( - 2 * 3 + 5) + ( - 2 * 4 + 5) + ( - 2 * 5 + 5)

This simplifies to


\sum_(k=3)^5( - 2k + 5) = ( - 6 + 5) + ( - 8+ 5) + ( - 10+ 5)


\sum_(k=3)^5( - 2k + 5) = ( - 1) + ( - 3) + ( - 5)


\sum_(k=3)^5( - 2k + 5) = - 9

User Renas
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.